2019
DOI: 10.1038/s41467-019-10745-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of TFIIH activation for nucleotide excision repair

Abstract: Nucleotide excision repair (NER) is the major DNA repair pathway that removes UV-induced and bulky DNA lesions. There is currently no structure of NER intermediates, which form around the large multisubunit transcription factor IIH (TFIIH). Here we report the cryo-EM structure of an NER intermediate containing TFIIH and the NER factor XPA. Compared to its transcription conformation, the TFIIH structure is rearranged such that its ATPase subunits XPB and XPD bind double- and single-stranded DNA, consistent with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
182
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(221 citation statements)
references
References 61 publications
14
182
0
Order By: Relevance
“…MSD analysis revealed that the long-range mode of linear diffusion had a significantly higher diffusion coefficient than the short-range mode. Although XPA has been reported to bind DNA as a homodimer on short DNA substrates 9 , volumes of XPA on a 538 bp DNA substrate measured by AFM in this study are consistent with the size of a monomer, in support of previous reports 15,21,36 . We also observed formation of a "dimer band" at high concentrations by EMSA, but this band is indistinguishable from a complex containing one XPA bound at the lesion and one bound at the DNA end (or two otherwise distinct monomeric binding events).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…MSD analysis revealed that the long-range mode of linear diffusion had a significantly higher diffusion coefficient than the short-range mode. Although XPA has been reported to bind DNA as a homodimer on short DNA substrates 9 , volumes of XPA on a 538 bp DNA substrate measured by AFM in this study are consistent with the size of a monomer, in support of previous reports 15,21,36 . We also observed formation of a "dimer band" at high concentrations by EMSA, but this band is indistinguishable from a complex containing one XPA bound at the lesion and one bound at the DNA end (or two otherwise distinct monomeric binding events).…”
Section: Discussionsupporting
confidence: 91%
“…XPA binds non-damaged DNA and dG-C8-AAF as a monomer. Previous reports suggest that XPA may bind DNA as a homodimer 9,35 while others indicate monomeric binding 15,21,36 . AFM offers the unique ability to distinguish between distinct complexes (e.g., one protein at a DNA end and one protein at a lesion) and true dimerization.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations